Reconstruction of Gingival Mask around CAD-CAM Bar and Ball Attachment in Implant-Retained Overdenture - Samira Naybandi Atashi; Somayeh Zeighami (Hindawi Limited, 2024)
Gingival mask is a copy of the peri-implant tissue, which plays an important role in the fabrication of an optimal restoration. Losing the gingival mask is a clinical problem that complicates the process of restoration fabrication. Herein, a simple precise technique is described step by step to solve this problem in the patient with CAD/CAM milled bar and ball attachment treatment plan for a maxillary and a mandibular implant-supported overdenture, without the need to repeat the entire clinical and laboratory procedures.